OPTIMALISASI PENGENALAN HIBAH PENDIDIKAN DAN DANA DESA PADA SEKOLAH DAN DESA CANDIPARI SIDOARJO - Tomy Michael (LPPM Universitas Bina Bangsa, 2023)
In the study of law there is always concern about the applicability of a statutory regulation. The concern, if explored further, is the inability to carry out responsibilities which can be caused by many things, including ignorance of what is being faced, inability to resolve legal issues resulting in rejection, inability due to cases that affect. Community service activities are carried out from January to February 2023. The purpose of community service is ultimately to provide an understanding for Candipari Village that receiving grants from universities is actually very helpful for the village in implementing its program. The grant funds referred to are like the Matching Fund where there are provisions in kind that villages generally already have so that the achievement of the program according to the current year's APBDes is achieved more quickly